Respons Masyarakat atas Komunikasi Non-Verbal Jamaah Tabligh: Studi Kasus di Kabupaten Sorong - Abdai, Faisal; Kahina, Dwi Iin (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2021)
This study aims to determine the form, meaning, and public reaction to nonverbal communication applied in the Da'wah of the Tablighi Jamaat and the definition contained in da'wah's symbols. The method used in qualitative research is by conducting observations and interviews. The data is then analyzed continuously, from the beginning of data collection until the last data collection. First, the results showed that the meaning of symbols in nonverbal communication in the Da'wah of the Tablighi Jamaat by its followers is considered a sunnah of the Prophet Muhammad. The nonverbal symbols shown are; greetings are shaking hands tightly, wearing robes and turbans, keeping a beard, siwak as a toothbrush, eating together in one container (tray), and eating with hands without using a spoon, and using perfume. Second, the public's response to the Da'wah of the Tablighi Jamaat is quite diverse. People who reject his symbol on the use of robes and turbans. This is because it is considered unethical to apply. The symbol of the beard, siwak, and eating together is considered by the community as a good thing. It's just that cleanliness is in question in society. People who accept nonverbal symbols in the Da'wah of the Tablighi Jamaat are the use perfume. The reason is the use of perfume because it shows cleanliness and a delicious aroma. He was sitting cross-legged, the most attractive symbol of society because it shows politeness and good etiquette.